Effect of insulin on human skeletal muscle protein synthesis is modulated by insulin-induced changes in muscle blood flow and amino acid availability - Fujita, Satoshi (2006)
Insulin promotes muscle anabolism, but it is still unclear whether it stimulates muscle protein synthesis in humans. We hypothesized that insulin can increase muscle protein synthesis only if it increases muscle amino acid availability. We measured muscle protein and amino acid metabolism using stable-isotope methodologies in 19 young healthy subjects at baseline and during insulin infusion in one leg at low (LD, 0.05), intermediate (ID, 0.15), or high (HD, 0.30 mU·min(−1)·100 ml(−1)) doses. Insulin was infused locally to induce muscle hyperinsulinemia within the physiological range while minimizing the systemic effects. Protein and amino acid kinetics across the leg were assessed using stable isotopes and muscle biopsies. The LD did not affect phenylalanine delivery to the muscle (−9 ± 18% change over baseline), muscle protein synthesis (16 ± 26%), breakdown, or net balance. The ID increased (P < 0.05) phenylalanine delivery (+63 ± 38%), muscle protein synthesis (+157 ± 54%), and net protein balance, with no change in breakdown. The HD did not change phenylalanine delivery (+12 ± 11%) or muscle protein synthesis (+9 ± 19%), and reduced muscle protein breakdown (−17 ± 15%), thus improving net muscle protein balance but to a lesser degree than the ID. Changes in muscle protein synthesis were strongly associated with changes in muscle blood flow and phenylalanine delivery and availability. In conclusion, physiological hyperinsulinemia promotes muscle protein synthesis as long as it concomitantly increases muscle blood flow, amino acid delivery and availability.